PERAN BUNDA CORLA SEBAGAI BRAND AMBASSADOR PRODUK MS GLOW DALAM MENINGKATKAN BRAND IMAGE RESELLER DI JEMBER - Eq Monica Ferliana; Sudahri (MEDIAKOM, 2023)
Ms Glow is the object of research because Ms Glow has successfully managed her business and developed her products since she was founded in 2013, starting from selling skincare and body care products through online platforms and has now expanded her reach by opening treatment clinics located in several big cities. After the selection of Bunda Corla as Ms Glow's brand ambassador, various opinions were expressed by the public on the social media platform Instagram regarding Mother Corla's competence in carrying out her responsibilities as a brand ambassador. This research aims to gather information from MS Glow Jember resellers regarding the role of Mother Corla as Brand Ambassador in improving the brand image of MS Glow products. This phenomenon is of concern to researchers so that research needs to be carried out on whether the impact and attractiveness of Mother Corla's role as Ms Glow's brand ambassador can improve brand image. Researchers have carried out interview activities which were carried out on August 2 2023 and interviewed MS Glow Resellers who were in Jember. In this interview, the researcher aims to gain in-depth insight into how significant the role of Ambassador Bunda Corla is in shaping consumer perceptions of the MS Glow brand and how this brand association influences resellers in Jember in the aspects of excellence, strength and uniqueness of the brand association. In this way, we can explore the important role of Ambassador Bunda Corla in shaping and improving the MS Glow brand image in the eyes of consumers and resellers. This research method is descriptive qualitative using Kennedy and Soemanaraga's 2006 Marketing Communication theory.